Macro-historical conditions for a reconciliation in East Asia remaking history in an age of civilizational crisis. - MUSHAKOJI, Kinhide (2014)
This article talks about how the dominant Westphalian model, which is rooted in the capitalist development, has failed to institute peace among the countries in different regions in the world—a product of a civilization’s crisis. This crisis is a confluence of expansionism and cultural imperialism wielded by the circle of “civilized nations,” which
Japan joined, resulted in the Great Japan Asianism, and fueled the development of Japan’s war state, the new Cold War between the haves and have-nots, and the growth of antihegemonic movements all over the world. Citing the 1955 Bandung conference as a precedent, the article seeks to establish alternatives to the Westphalian peace
narrative and suggests that Asian nations, in particular, look inwards and find amongst themselves local and indigenous means to achieve peace. This also calls for a reconciliation among the four countries of East Asia to look beyond the historical transgressions of the past and move forward towards building a pluralistic “common home of East Asian peoples.”
Keywords: Bandung conference; Westphalian model